2016
DOI: 10.1007/s11199-016-0647-5
|View full text |Cite
|
Sign up to set email alerts
|

Gender Roles and Stereotypes about Science Careers Help Explain Women and Men’s Science Pursuits

Abstract: Diverse perspectives in science promote innovation and creativity, and represent the needs of a diverse populace. However, many science fields lack gender diversity. Although fewer women than men pursue careers in physical science, technology, engineering, and mathematics (pSTEM), more women than men pursue careers in behavioral science. The current work measured the relationship between first-year college students' stereotypes about science professions and course completion in science fields over the next 3 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 28 publications
2
40
0
5
Order By: Relevance
“…Stereotypes about people who are interested in STEM abound in popular culture, making it one of the largest barriers for women (Moss-Racusin, Molenda, and Cramer 2015;Ryan 2014). Women in STEM face gender stereotypes at both community colleges (Kincaid 2015) and universities (Schneider 2010;Stout, Grunberg, and Ito 2016). Because of the long-standing sociocultural stereotypes regarding successful cisgender white males and academic STEM disciplines, women face a phenomenon known as stereotype threat (Chase 2012;Corbett and Hill 2015).…”
Section: Stereotypesmentioning
confidence: 99%
“…Stereotypes about people who are interested in STEM abound in popular culture, making it one of the largest barriers for women (Moss-Racusin, Molenda, and Cramer 2015;Ryan 2014). Women in STEM face gender stereotypes at both community colleges (Kincaid 2015) and universities (Schneider 2010;Stout, Grunberg, and Ito 2016). Because of the long-standing sociocultural stereotypes regarding successful cisgender white males and academic STEM disciplines, women face a phenomenon known as stereotype threat (Chase 2012;Corbett and Hill 2015).…”
Section: Stereotypesmentioning
confidence: 99%
“…A third explanation, which we derived from previous research, suggests that women think negatively about careers in technology and that this thinking is reinforced over time (Master et al, 2016;Stout et al, 2016). An experiment conducted with high school students in the US found that female students reacted more positively to computer classrooms that exhibited fewer artifacts associated with traditional computer science (i.e., Star Trek posters, stray equipment parts, science fiction books, video games) and incorporated more neutral objects (i.e., art and nature posters, water bottles, general magazines, plants), which resulted in their being more willing to take a high school class in computer science (Master et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last two decades, many studies have queried women about their interest in technology-related disciplines using surveys, focus groups, and direct interviews (Beyer, 2008(Beyer, , 2014Buschor, Berweger, Frei, & Kappler, 2014;Cory, Parzinger, & Reeves, 2006;Geyfman, Force, & Davis, 2016;Joshi & Schmidt, 2006;Merhout, Havelka, & Rajkumar, 2016;Stout, Grunberg, & Ito, 2016;Wang et al, 2015;Zhang, 2007). These studies have found that parental influence, role models, stereotypes, knowledge of the field, influence of peers, self-efficacy, and external encouragement are important factors that affect women's interest in IS.…”
Section: Figure 1 Percent Of Female Employees At Selected Technologymentioning
confidence: 99%
See 2 more Smart Citations